Meningkatkan Hasil Belajar Peserta Didik Kelas VII pada Materi Kemampuan dan Keterbatasanku Melalui PBL di SMP Negeri 02 Ketungau Hilir Tahun Ajaran 2024/2025 - Maria Mahdalena (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2024)
The provision of high-quality education is significantly influenced by key factors, specifically educators and students. Competent educators are likely to cultivate quality individuals, adhering to the philosophy that "people can only share and give to others what they possess." In the teaching and learning process, one of the key elements that facilitates successful learning is the Problem-Based Learning (PBL) model, which significantly enhances student independence, interest, and motivation in their educational pursuits. According to observations conducted by researchers at SMP Negeri 02 Ketungau Hilir, particularly in class VII, it has been determined that in Catholic Religious Education, teachers predominantly employ teacher-centered learning methods and have yet to implement the Problem-Based Learning (PBL) model. This approach has adversely impacted student learning outcomes, resulting in the failure to meet minimum completion criteria. Based on the findings from data analysis and discussions in this study, it can be concluded that the results regarding the enhancement of learning outcomes indicate a sustained improvement in Cycle II, where student performance rose by 82% from Cycle I to 100%. The average student score increased from 79.06 in Cycle I to 84.37 in Cycle II.